1982
DOI: 10.1055/s-2007-971454
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Properties of Tropine Dehydrogenase from Root Cultures ofDatura stramonium

Abstract: From sterile root cultures of Datura stramonium, an NADP(H)-specific tropine dehydrogenase has been isolated and characterized. The enzyme catalyzes the reversible and stereospecific oxidation of tropine and related tropane-3 alpha-ols to the corresponding ketone. Isomeric pseudotropine (tropane-3 beta-ol) is neither accepted as substrate nor produced in the reverse reaction. It is assumed that this dehydrogenase is involved in the biosynthesis of tropane alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Two stereospecific NADPH-dependent reductases, tropinone reductase TR-I and TR-II, constitute a branching point in the biosynthesis of tropane alkaloids: TR-I catalyses the stereospecific reduction of tropinone to tropine, whereas TR-II reduces tropinone to pseudotropine (Koelen and Gross 1982;Drager et al 1988). Hashimoto et al (1992) previously characterized TRs that had been purified from cultured roots of H. niger and showed that the two TRs had both common and different biochemical and kinetic properties.…”
Section: Gene Cloningmentioning
confidence: 99%
“…Two stereospecific NADPH-dependent reductases, tropinone reductase TR-I and TR-II, constitute a branching point in the biosynthesis of tropane alkaloids: TR-I catalyses the stereospecific reduction of tropinone to tropine, whereas TR-II reduces tropinone to pseudotropine (Koelen and Gross 1982;Drager et al 1988). Hashimoto et al (1992) previously characterized TRs that had been purified from cultured roots of H. niger and showed that the two TRs had both common and different biochemical and kinetic properties.…”
Section: Gene Cloningmentioning
confidence: 99%
“…The order of elution was tropinone, tropine, i-tropine, and nicotine. After TR-I and TR-II were completely separated by column chromatography, the enzyme activities were measured by the consumption of NADPH at 340 nm (5,15). The concentration of NADPH in the above reaction mixture was lowered to 0.2 mm to maintain low background absorbance.…”
Section: Plant Materialsmentioning
confidence: 99%
“…An NADPH-dependent oxidoreductase (TR3-I; Fig. 1) that converts tropinone to tropine was first discovered in cultured roots of Datura stramonium (15), but a similar enzyme with different stereospecificity that reduces tropinone to 4I-tropine (TR-II) was later found in cultured roots of Hyoscyamus niger (5). Subsequent studies by us (23) and others (4) indicated that the two stereospecifically distinct reductase activities can coexist in a given alkaloid-producing species.…”
mentioning
confidence: 99%
“…A second stereospecific activity, TR II, reduces tropinone to pseudotropine [9]. There was prolonged uncertainty as to whether the reduction of tropinone represented one or two separate prott .,as [7][8][9].…”
Section: Introductionmentioning
confidence: 99%